Enhancing intermittent exercise performance through brief sole cryostimulation during breaks in a hot environment - XiaoYue Hu; Yutaro Nakagawa; Kazuyuki Kanatani; Takashi Kawabata (Journal of Exercise Science & Fitness, 2025)
Objectives: This study aimed to evaluate the efficacy of brief cryostimulation of the soles of the feet on exercise performance, thermoregulation, and cardiovascular function during an inter-exercise rest period in a hot environment. Methods: Eight physically active and healthy adults (6 males, 2 females; mean age: 24.89 ± 3.10 years) participated in this randomized crossover self-controlled study. To determine exercise intensity, the maximal oxygen uptake (VO2max) test was conducted as a preliminary step. After a minimum 72-h interval, participants performed intermittent cycling consisting of two phases. The first phase included 15 min of steady-state exercise (SSE) at 70 % VO2max, followed by 15 min of maximal cycling effort (MCE) (≥70 % VO2max). Participants then rested in a seated position for 10 min, during which they were randomly assigned to one of two conditions: CON (stationary rest) or Sole-Cryo (2-min sole cryostimulation using a −50 °C ice pack). After the rest period, they proceeded to the second phase, completing a time-to-exhaustion (TTE) test at an intensity exceeding 70 % VO2max. All exercise sessions were conducted in a hot environment (35 °C, 60 % relative humidity). During the experiment, esophageal temperature (Tes), skin temperature (Tsk), thigh muscle temperature (TMT), skin forearm blood flow (Skin FBF), heart rate (HR), stroke volume (SV), and cardiac output (CO) were continuously monitored. The ratings of perceived exertion (RPE) and thermal sensation (TS) were recorded every 2-min. Results: Time to exhaustion was significantly longer in the Sole-Cryo condition compared to the CON condition (CON: 3.23 ± 1.07 min vs. Sole-Cryo:3.92 ± 1.10 min, p < 0.01). In contrast, Tes showed no significant difference between conditions (p > 0.05). During the 10-min resting period, both Tsk (CON: 37.25 ± 0.36 °C vs. Sole-Cryo: 36.60 ± 0.42 °C, p < 0.05) and skin FBF (CON: 12.57 ± 2.71 ml/min/100 ml vs. Sole-Cryo: 10.89 ± 2.25 ml/min/100 ml, p < 0.05) were significantly lower in the Sole-Cryo condition. However, TMT, HR, SV, and CO remained unchanged between conditions (p > 0.05). Additionally, at the 52 nd min of PT, both RPE (CON: 19.37 ± 0.74 vs. Sole-Cryo: 16.88 ± 1.26, p < 0.05) and TS (CON: 3.75 ± 0.46 vs. Sole-Cryo: 2.75 ± 0.46, p < 0.05) were significantly lower in the Sole-Cryo condition. Conclusions: Brief cryostimulation interventions applied to the soles during rest periods in a hot environment did not significantly affect core body temperature or the cardiovascular system. However, it lowered Tsk and skin FBF and improved perceptual responses such as RPE and thermal sensation. These improvements may have contributed to the enhancement of time to exhaustion.